EARTHQUAKE VULNERABILITY MAPPING BASED ON MICROSEISMIC MEASUREMENTS IN THE CAMPUS AREA OF UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA - Purnama, Aditya Yoga; Nurhanafi, Kholis; Susanti, Susanti; Wibowo, Nugroho Budi; Perdhana, Radhitya (Engineering Faculty Universitas Lampung, 2025)
Building damage caused by earthquakes is more prevalent in the sedimentary areas of Yogyakarta City compared to the hilly regions of Wonosari and Kulonprogo, which have harder soil layers. The campus of Universitas Sarjanawiyata Tamansiswa (UST) is one of the campuses located in Yogyakarta City, where the regional geology is dominated by the Merapi Young Volcanic Deposits Formation. The UST campus area is vulnerable to earthquakes due to its proximity to an active seismic zone, making earthquake vulnerability mapping based on microseismic data an important necessity to support disaster mitigation efforts. The microseismic method was used in this study, while data analysis employed the Horizontal-to-Vertical Spectral Ratio (HVSR). Microseismic measurements were chosen because they have the advantage of not damaging the surface conditions of the ground, thus preserving the environment, and are easy to use in urban areas. The research method stages include survey design, field data collection, data processing and interpretation, and the creation of earthquake vulnerability maps. Data points were collected from 7 locations covering the Universitas Sarjanawiyata Tamansiswa campus area. The research results indicate that the study area has a dominant frequency value ranging from 1.10 to 2.74 Hz. Meanwhile, the amplification value ranges from 1.25 to 2.2. The sediment thickness of the study area ranges from 32 to 79 meters. The Seismic Vulnerability Index (Kg) of the study area ranges from 0.57 to 4 on a low to high scale. Based on the dominant frequency values, amplification, and seismic vulnerability index, the areas of the UST campus that are more vulnerable to earthquakes are the northern, eastern, and central parts, while the southern part is relatively safer.